Empirical modeling of dynamic grinding force based on process analysis. Issue 9 (October 2016) - Guo, Miaoxian; Li, Beizhi; Ding, Zishan; Liang, Steven
Abstract Dynamic force modeling can quantitatively describe the force with amplitude-frequency characteristic and facilitate understanding of the influence of grinding parameters on dynamic performance. This research attempts to build up dynamic grinding force models through empirical approaches. In the paper, the related parameters in the empirical model are studied based on the fact that the dynamic grinding force is due to the dynamic change of depth of cut and the dynamic model of grinding process developed in previous studies. Then grinding force model is established using the process parameters like wheel speed, feed rate, and dynamic change of depth of cut. At last, the coefficients are determined experimentally and the models are verified at specified conditions. The grinding parameters, the dynamic process of the grinding, and the machine tool conditions are taken into account in the paper. The empirical model developed in this paper can be used to predict the variation of the dynamic grinding force during process. This model can also be used to guide the selection of grinding conditions and to develop the machine tool for dynamic performance optimization.